2017
DOI: 10.2214/ajr.17.18170
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Radiation Force Impulse Elastography in Determining the Effects of Type 1 Diabetes on Pancreas and Kidney Elasticity in Children

Abstract: The current study showed no significant difference in the shear-wave velocity of kidneys in children with type 1 diabetes with normoalbuminuria compared with the healthy control subjects. We also observed that the shear-wave velocity of the pancreas in children with type 1 diabetes and healthy control subjects did not differ significantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 18 publications
1
13
1
1
Order By: Relevance
“…This finding agrees with our results for that region. They reported Vs of 1.09 ± 0.22 m/s for the body of the pancreas in healthy control subjects and 0.99 ± 0.25 m/s for patients with type 1 diabetes – values slightly lower than we found in our patients [7].…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…This finding agrees with our results for that region. They reported Vs of 1.09 ± 0.22 m/s for the body of the pancreas in healthy control subjects and 0.99 ± 0.25 m/s for patients with type 1 diabetes – values slightly lower than we found in our patients [7].…”
Section: Discussioncontrasting
confidence: 87%
“…Nevertheless, in contrast to their study, we did not find any correlation between Vs and BMI. Nor did we determine a correlation between the Vs and the duration of diabetes ( p = 0.7534), a finding which agrees with the results published by Saglam et al [7].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Another study evaluating [37] the kidneys' renal cortical stiffness in Type 2 diabetes with grade 3-4 diabetic nephropathy showed that SWV was also higher than that in the control subjects. Saglam et al [38] evaluated the effects of Type 1 diabetes on renal cortical elasticity. They did not find any significant difference in SWV between patients with Type 1 diabetes and healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Tüm bu hastalıklarsa böbrek KS artmaktadır. Tip I ve Tip II DM olan hastalarda normo-albuminurik döneminde böbrek KS kontrollere benzer iken, albumunüri varlığında böbrek KS arttığı bildirilmiştir(30)(31)(32). ElastPQ tekniği doku elastikiyetini değerlendiren son elastografi tekniğidir ve çocuklarda böbrek hastalıklarda doku elastikiyeti bu teknik ile ilk kez 2016 yılında Xu ve ark(33) tarafından yapılmıştır(33).…”
unclassified